A Need Analysis on Technology for Teaching English to Primary School Students with Specific Learning Difficulties - Bite Tandi Rapa, Inricael; Algi Gaffar Faridha, Haidir (Mutiara: Multidiciplinary Scientifict Journal, 2025)
This study was motivated by the challenges faced by teachers in teaching English to primary school students with specific learning difficulties (SpLDs). With the increasing need to use technology in education, the purpose of this study was to analyze the application of technology in teaching English to students with SpLDs at SD Negeri 010 Samarinda Seberang. The method used was semi-structured interviews with two special assistant teachers to understand the teaching practices and technology applied. The results showed that although teachers use applications such as Canva and Pinterest to create worksheets and teaching materials, the technology applied is still limited and does not fully meet the needs of students with SpLDs. Teachers focus more on basic exercises such as alphabet recognition and vocabulary, but the existing technology does not help enough in improving students' reading, writing and speaking skills. The conclusion of this study emphasizes the importance of integrating more specialized and personalized applications in English language teaching for students with SpLDs. Recommendations are given to use assistive applications designed to support various learning difficulties, to improve learning effectiveness and student motivation.